Longitudinal brain health and neurological correlates of sexual strangulation in young adults: Study protocol for a prospective cohort study - Keisuke Kawata; Claire V. Buddenbaum; Megan E. Huibregtse; Sage H. Sweeney; Hu Cheng; Molly Rosenberg; Debra Finn; Sharlene D. Newman; Grace M. Wetzel; Jenna M. Hohne; Kirstin M. West; Molly McGuire; et al. (PLoS ONE, 2026)
Sexual strangulation (also referred to as choking during sex) has become increasingly prevalent among young adults and disproportionately affects females. Epidemiological studies indicate that more than half of college-aged women report a lifetime history of being strangled during sex, and it is most often described as consensual. Despite its widespread occurrence, little is known about the acute and cumulative neurological consequences of this behavior. Pilot studies suggest associations between frequent sexual strangulation and elevations in blood biomarkers of neural injury, alterations in brain structure and connectivity, and increased mental health symptoms; however, existing evidence is limited by cross-sectional designs, short-term follow-ups, and small sample sizes. This prospective cohort study is designed to characterize both the acute and longitudinal neurological effects of sexual strangulation using multimodal assessments. A total of 200 young adult females (100 with frequent sexual strangulation exposure and 100 controls with no lifetime strangulation history), along with a pilot cohort of 40 males, will undergo comprehensive evaluations including blood-based biomarkers of neural injury and inflammation, multimodal MRI, cognitive and oculomotor testing, retinal imaging, and mental health assessments. Acute neurological responses will be assessed approximately 24 hours following a sexual event involving strangulation (or non-strangulation sex in controls), while longitudinal follow-up will occur every six months over 30 months to examine cumulative exposure effects. Semi-structured interviews conducted at each time point will characterize strangulation practices, contextual factors, consent dynamics, and associated symptoms. The primary objectives are to (1) examine baseline group differences in neurological health between individuals with frequent sexual strangulation exposure and non-strangulation controls, (2) identify acute neurological alterations following sexual strangulation, (3) determine associations between cumulative strangulation exposure and neural cellular, physiological, and functional integrity over time, and (4) characterize young adults’ experiences, contextual factors, and perceptions of sexual strangulation through semi-structured interviews. Collectively, this study aims to establish temporal relationships between sexual strangulation and neurological health outcomes and to inform clinical guidance, sexual health education, and harm-reduction strategies related to this increasingly common sexual practice.